Do-It-Yourself Microsuture from Human Hair for Basic Microsurgical Training - Luangjarmekorn, Pobe; Kitidumrongsook, Pravit; Honsawek, Sittisak (Journal of Reconstructive Microsurgery, 2019)
Background Microsuture is an essential material for basic microsurgical training. However, it is consumable, expensive, and sometimes unavailable in the microsurgical laboratory. To solve this problem, we developed a microsuture made from human hair and needle gauge.Methods Do-It-Yourself (DIY) microsuture is made from human hair and needle gauge 32G (BD Ultra-Fine Pen Needles 4 mm × 32G). Methods are explained step by step. This DIY microsuture (labeled as “test microsuture”) and nylon 8–0 (Ethilon suture 8–0, labeled as “standard microsuture”) were used for teaching orthopaedic residents to perform arterial anastomosis in chicken thighs. All residents practiced without knowing that “test microsuture” was made from the DIY method. After completing the training, quality of both microsutures was evaluated by questionnaire in topics of (1) thread quality (size, strength, elasticity, handing, knot perform, and knot security), (2) needle quality (size, curve, shape, sharpness, handling, and strength), (3) needle–thread interface (size, strength, and smoothness), and (4) overall quality of microsuture. Each category was evaluated by Likert score (5 = excellent, 4 = good, 3 = fair, 2 = poor, and 1 = very poor).Results The DIY microsuture was performed in three steps: (1) insert human hair into needle gauge by microforceps, (2) bend needle into smooth curve, and (3) disconnect needle and create needle–hair interface. The questionnaire was completed by 30 orthopaedic residents and showed that thread quality of DIY and standard microsuture had “good” and “good-to-excellent” quality (mean Likert score: 3.77–4.23 and 3.80–4.27, respectively, with no statistical difference). Thread–needle interface quality of DIY and standard microsuture also had “good” and “good-to-excellent” quality (Likert score: 3.73–4.20 and 4.07–4.33, respectively, with no statistical difference). Needle part of DIY microsuture had lower quality than standard suture (fair-to-good compared with good-to-excellence quality, score 3.30–3.67 vs. 4.20–4.27, respectively, with a statistically significant difference, p-value < 0.05). However, overall quality of DIY suture and standard microsuture had “good” and “good-to-excellent” (mean Likert score: 3.73 and 4.00, respectively, with no statistical difference).Conclusion The DIY microsuture from human hair and needle gauge could be an alternative for basic microsurgical training with lower cost, easy production, and more availability for use in practice with acceptable quality compared with that of standard microsuture.
Keywords: hair; microsuture; microsurgery